The view from the ‘other side of the desk’ - Galvin, Peter (Cambridge University Press, 2014)
This issue will be the last for me in the role of Editor-in-Chief. My 3 years in the role (2012–2014) have seen the Journal undergo significant changes. I will not detail these at this point, but moving to the Scholar One manuscript management system in 2012 followed by Cambridge Journals taking over as the publisher of Journal of Management & Organization in 2013 has put the Journal on a new and very strong trajectory.What is more likely to be of interest for most people are some of my insights from my time as an editor. Before I stepped into any sort of editorial role, I had a number of assumptions about the way the journal system worked, how decisions were made and the roles that the senior people running the journals actually undertook. Many of these proved to be wrong and understanding what happens on the ‘other side of the desk’ may assist all people involved with, or submitting to journals.